MANAJEMEN KURIKULUM SEKOLAH MENENGAH PERTAMA - Muliana Muliana Muliana (Manajer Pendididikan, 2016)
The Purpose of this reseach is to improve the implementation of learning curiculum management of junior high school. The spesipic problem of this reseach is how to do the curiculum lerion and some problem implementation of learning junior of high school inmuhammdiyah. The method used in this research is descriptive qualitative, data collection techniques by observation, interview and documentation. This research subject is principal, viceprincipal,foundation, leader, teachers and student Conclusion. Of this study is implementation of learning curiculum management of lerson plan have learn of the condition of the school.Keywords: curiculum, management